2006
DOI: 10.11609/jott.zpj.1519.2459-61
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections in wild herbivores in the Mahendra Choudhury Zoological Park, Chhatbir, Punjab

Abstract: The present investigation was undertaken to study the parasitic infections in herbivores kept at Mahendra Choudhury Zoological Park, Chhatbir in Punjab, India. The occurrence and intensity of gastrointestinal parasitic load in 169 animals of 16 different herbivore species belonging to the families Cervidae, Bovidae, Hippopotamidae, Elephantidae, Rhinocerotidae and Equidae was determined by standard qualitative and quantitative parasitological techniques. The overall occurrence of gastrointestinal parasites bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
3
15
1
Order By: Relevance
“…was recorded in all herbivores of the zoo. The present findings differ from the report of Singh [24] who recorded infection as the most commonly detected parasitic infection (89%) in wild herbivores in the Mahendra Choudhury zoological park, Chhatbir, Punjab. The prevalence of parasitic infection in rhesus macaques under primate category was 60%.…”
Section: Cervus Unicolor Ascariscontrasting
confidence: 99%
“…was recorded in all herbivores of the zoo. The present findings differ from the report of Singh [24] who recorded infection as the most commonly detected parasitic infection (89%) in wild herbivores in the Mahendra Choudhury zoological park, Chhatbir, Punjab. The prevalence of parasitic infection in rhesus macaques under primate category was 60%.…”
Section: Cervus Unicolor Ascariscontrasting
confidence: 99%
“…A total of 9 parasite taxa were identified both in December and in April, of which 6 (66.67%) and 3 (33.33%) were helminthes and protozoa respectively ( (Table 3). In agreement with this study, many previous works reported mixed infections in wild animals in captivity [7]. Otegbade and Morenikeji [26] reported that that mixed infections may consists of two or more parasites.…”
Section: Identification Of Species Of Gastrointestinal Parasitessupporting
confidence: 92%
“…In captivity, animals appear to be less resistant to parasitic infections than under their natural habitats [4]. The changes in environment and living conditions from the natural habitat to captivity alter the life styles of animals, reduce disease resistance ability and increase their susceptibility to parasitic infections [5] [6] [7]. Vulnerability of captive wild animals to parasitic infections depends on factors, like feeding, keeping conditions, animal management and environmental conditions, such as temperature and humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of the infection by means of oocyst per gram revealed mild to severe infection of Eimeria sp. ranging from 300-2300 with an average of704.35 ± 107.72 which is in close approximation with the findings of Singh et al, (2006).…”
Section: Resultssupporting
confidence: 88%